Measurement of the top-quark mass in tt¯ + 1-jet events collected with the ATLAS detector in pp collisions at √s = 8 TeV - Onofre, A. (2019)
A determination of the top-quark mass is presented using 20.2 fb−1 of 8 TeV proton-proton collision data produced by the Large Hadron Collider and collected by the ATLAS experiment. The normalised differential cross section of top-quark pair production in association with an energetic jet is measured in the lepton+jets final state and unfolded to parton and particle levels. The unfolded distribution at parton level can be described using next-to-leading-order QCD predictions in terms of either the top-quark pole mass or the running mass as defined in the (modified) minimal subtraction scheme. A comparison between the experimental distribution and the theoretical prediction allows the top-quark mass to be extracted in the two schemes. The value obtained for the pole-mass scheme is: mtpole=171.1±0.4(stat)±0.9(syst)−0.3+0.7(theo)GeV The extracted value in the running-mass scheme is: mt(mt)=162.9±0.5(stat)±1.0(syst)−1.2+2.1(theo)GeV. The results for the top-quark mass using the two schemes are consistent, when translated from one scheme to the other. [Figure not available: see fulltext.]